Paul’s designations of God in Romans - Au, Wing Yi (The University of Edinburgh, 2021)
This thesis investigates one aspect of Paul’s God-languages, namely, Paul’s divine designations of θεός in his letter to the Romans. By comparing and contrasting Paul’s designations with his Jewish and pagan contemporaries, this thesis argues that Paul creatively reinterprets and adapts the socio-linguistic resources of divine epithets to justify for the incorporation of Gentiles in God’s salvation. Despite a presumed or neglected “preconceived understanding” of Paul’s God in Pauline scholarship, this study begins with an observation that Paul’s divine designations are neither ordinary nor precedented in Jewish tradition. Inspired by a systemic-functional linguist, Jay Lemke’s model of thematic meaning, divine designations are taken as sociolinguistic phenomenon. The meanings of Paul’s designations are first studied in the respective arguments in Romans. Then, they are compared to the recurrent linguistic patterns of divine epithets found in the OT, early Jewish, and pagan texts. Although exact parallels of Paul’s designations are absent in Jewish tradition, striking linguistic resemblance is found between Greco-Roman texts and Romans. Paul does not make up these epithets out of nothing, nevertheless, their thematic meanings divert from its pagan usage. Paul’s designations in Romans trace God’s essential salvific activities that allows for the incorporation of Gentiles. While God is the Father of Davidic kings in the OT, God’s Fatherhood (Rom 1:7; 6:4; 8:15; 15:6) is reinterpreted in terms of his redeeming acts on the cross. Yet, the Father’s promise concerning Israel’s blessing of adoption is not redirected but expanded to the Gentiles. As for εἷς ὁ θεός (3:30), Paul contends the impartiality of the one God who justifies Jews and Gentiles alike on the same basis of faith. Besides the scope of God’s justifying activities, four interconnected designations in 4:5, 17b, 24 are employed to justify the place of the ἔθνη in Abraham’s family, Paul’s mission as well as God’s eschatological kingdom. In Romans 9: 12, 16, the designations highlight God’s incongruous call and mercy are what constitute, create, and sustain Israel from the beginning. In Romans, the same divine call and mercy incorporate Gentiles into God’s community of salvation in the same way. In 15:5, the theological vision of divine ὑπομονῆς and παρακλήσεως illustrates a transformation from judgmental divisive minds into one conformed mind. The result of unified worship is confirmed in “the God of hope”, configuring God’s eschatological hope for the Gentiles (15:13). In the last two designations ὁ θεὸς τῆς εἰρήνης (15:33; 16:20a), Paul reassures that any threats to the community of God’s people will be ultimately “pacified” by the conquering warrior God. For Paul, the God of Israel, especially in the OT and Romans, never falters in fulfilling his role as the Father, redeemer, justifier, reviver, mercy-giver, and warrior to create, rescue, and restore his people. However, compared with his Jewish and pagan contemporaries, Paul’s designations put special emphasis on the inclusion of ἔθνη in God’s universal salvation community.
Keywords: Pauline theology; designations; names; titles; Romans; Letter to the Romans; Gentile inclusion; Pauline epistles